the Pengaruh Kualitas Pelayanan Kefarmasian Terhadap Kepuasan Pasien Di Apotek Adapotek Daerah Denpasar: Pengaruh Kualitas Pelayanan Kefarmasian Terhadap Kepuasan Pasien Di Apotek Adapotek Daerah Denpasar - Yolanda Wibowo (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
Pharmacies are the closest pharmaceutical service facilities to the community, playing a crucial role in the procurement, storage, and dispensing of medications, as well as providing medication information (Ministry of Health of the Republic of Indonesia, 2016). The high preference of patients for the nearest pharmacy (Sujono et al., 2020) and the need for medications indicate the importance of optimal pharmaceutical services, including Medication Information Services (MIS). This study aims to evaluate respondent characteristics and analyze the relationship between pharmacy service quality based on five dimensions (Reliability, Responsiveness, Assurance, Empathy, and Tangible) and patient satisfaction at the Denpasar Regional Pharmacy. This study uses a descriptive observational design to describe the level of satisfaction with services at the Denpasar Regional Pharmacy. Data were collected from 95 respondents who were pharmacy patients. Data analysis includes a description of respondent characteristics and correlation tests to determine the relationship between service quality dimensions and patient satisfaction. Respondent characteristics showed that the majority were aged 17–27 years (54.6%), male (63.8%), high school educated (62.9%), and self-employed (54.3%). Most respondents (95.9%) had visited more than five times. The correlation analysis results showed that the dimensions of Responsiveness (p=0.003) and Assurance (p=0.001) had a significant relationship with patient satisfaction. Meanwhile, the dimensions of Reliability (p=0.998), Empathy (p=0.999), and Tangible (p=0.992) were not significantly correlated with patient satisfaction. The characteristics of consumers at Adapotek Daerah Denpasar are dominated by young age, male gender, high school education, and entrepreneurship with high visit frequency. Service quality aspects such as responsiveness (speed and willingness to help) and assurance (guarantee of trust and knowledge) significantly influence patient satisfaction. However, the dimensions of reliability, empathy, and tangibles do not show significant correlations, indicating that these aspects may require further attention to enhance overall patient satisfaction.